Profil Komunikasi dan Profil Kerjasama Lulusan Program Studi Pendidikan Biologi Universitas Terbuka - Dyah Aniza Kismiati; Leonard R. Hutasoit; Anna Ratnaningsih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
The success of a study program in a university can be seen from the quality of the graduates. If the quality and performance of graduates are good, the study program can be said to be successful. This is also true in remote collegesuch as the Universitas Terbuka. In order to know this, this study was conducted which aimed to determine the performance of graduates of the Biology Education Study Program, especially on the profile of communication ability and the ability to work with graduates. The sample of this study was 35 graduate users. This sample was obtained from a random sampling technique. Data is obtained through questionnaires and interviews conducted with graduates and graduate users. Next, the data are analyzed descriptively. The results showed that the profile of communication ability and cooperation of graduates was considered very good both of from the self-reflection of graduates and from graduate users. This is based on descriptive data analysis where graduates and graduate users strongly agree and agree with all statements in the profile of communication and cooperation skills.